MiRNAs and inflammatory bowel disease: An interesting new story. Issue 4 (11th November 2018) - Moein, Soheila; Vaghari‐Tabari, Mostafa; Qujeq, Durdi; Majidinia, Maryam; Nabavi, Seyed Mohammad; Yousefi, Bahman
Abstract: Inflammatory bowel disease (IBD), as a chronic and recurrent inflammatory disorder, is caused by a dysregulated and aberrant immune response to exposed environmental factors in genetically susceptible individuals. Despite huge efforts in determining the molecular pathogenesis of IBD, an increasing worldwide incidence of IBD has been reported. MicroRNAs (miRNAs) are a set of noncoding RNA molecules that are about 22 nucleotides long, and these molecules are involved in the regulation of the gene expression. By clarifying the important role of miRNAs in a number of diseases, their role was also considered in IBD; numerous studies have been performed on this topic. In this review, we attempt to summarize a number of studies and discuss some of the recent developments in the roles of miRNAs in the pathophysiology, diagnosis, and treatment of IBD. Abstract : MicroRNAs (miRNAs) are a set of noncoding RNA molecules that are involved in the regulation of the gene expression. We discussed the critical roles of some miRNAs in the pathophysiology, diagnosis, and treatment of IBD.